KAJIAN PENERAPAN GOOD MANUFACTURING PRACTICE (GMP) DI INDUSTRI KERUPUK IKAN SRESEH KABUPATEN SAMPANG MADURA - Hidayati, Darimiyya; Purwandari, umi; -, ihsannudin (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 2 (2022): Juni, 2022)
The demands of today's consumers are not only for quality but also for safe food. To improve product safety, “Industri Kecil Menengah” (IKM) must start implementing the basic level of feasibility, namely Good manufacturing practice (GMP). GMP is a basic feasibility standard that can be used to assess the level of industry feasibility. The purpose of this study was to determine the basic feasibility level of the two fish cracker industries located in Sreseh District, Sampang Regency. The research was conducted by direct observation in the field and interviews with the company's management. There are 14 elements of GMP whose feasibility level is measured based on the guidelines issued by the Food and Drug Administration (BPOM). The results of the assessment show that serious and critical discrepancies are still found so that both industries are included in the level IV category. To improve product safety, SMIs should start implementing the basic level of eligibility, namely GMP.